Comparative Study of Verses on the Creation of Women from the Perspective of Buya Hamka and Faqihuddin Abdul Kodir - Nurul Isra H (Yayasan Pesantren Mahasiswa An-Nur, 2024)
This research examines the concept of the creation of women in the Quran by comparing two interpretations from Buya Hamka and Faqihuddin Abdul Kodir, who employ different interpretative methods, namely the taḥlīlī method and the mubādalah method. The research method used is descriptive qualitative with a literature study, which is then analyzed comparatively to identify the similarities and differences in the views of these two figures. The difference in interpretation lies in Buya Hamka's focus on gender or sex differences, whereas Faqihuddin Abdul Kodir interprets verses related to the creation of women by focusing on the general meaning of these verses. Both agree that women are created from the same elements as men. In his work, Tafsir al-Azhar, Buya Hamka offers a different perspective on the authentic hadith used by mufassir, interpreting it as a metaphor or majazī meaning. Meanwhile, Faqihuddin Abdul Kodir's interpretation, using the mubādalah or 'mutuality' method, explains that there is no explicit indication in the verses that women's creation comes from men. He also argues that the authentic hadith regarding the 'rib' is merely a metaphor and adds that characteristics or traits like the 'rib' are inherent in every human being without distinction or specificity to a particular gender.